Design Flaws and Service System Breakdowns. Learning from Systems Thinking - Ing, David (FormAkademisk, 2014)
In what ways might systems thinking be helpful to designers? In the 21st century, the types of projects designers have engaged have expanded to include service systems. Service systems are typically composites of mechanisms, organisms, human beings and ecologies. Systems thinking is a perspective with theories, methods and practices that enables transcending disciplinary boundaries. Application of systems thinking in designing a service system can aid in surfacing potential flaws and/or anticipating future breakdowns in functions, structures and/or processes. Designers and systems thinkers should work together to improve the nature of service systems. As a starter set into these conversations, seven conditions are proposed as starting contexts. These conditions are not presented as rigourously defined or as exhaustive, but as an entry point into future joint engagement.